2023
DOI: 10.3389/fimmu.2023.1118721
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors 2, 4, and 9 modulate promoting effect of COPD-like airway inflammation on K-ras-driven lung cancer through activation of the MyD88/NF-ĸB pathway in the airway epithelium

Abstract: IntroductionToll-like receptors (TLRs) are an extensive group of proteins involved in host defense processes that express themselves upon the increased production of endogenous damage-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs) due to the constant contact that airway epithelium may have with pathogenic foreign antigens. We have previously shown that COPD-like airway inflammation induced by exposure to an aerosolized lysate of nontypeable Haemophilus influenzae (NTHi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Consequently, airway patency improves, bronchospasm is reduced, and expiratory flow rates and maximal ventilatory volumes increase [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, airway patency improves, bronchospasm is reduced, and expiratory flow rates and maximal ventilatory volumes increase [14,15].…”
Section: Discussionmentioning
confidence: 99%
“… 53 The antitumor activity of TLR agonists was first reported as early as the 18th century when bacterial infections had the potential to inhibit cancer progression. 54 TLR4 agonists, such as the BCG vaccine, imiquimod, and lipid monophosphate A, have been approved by the FDA for immunotherapy of superficial migratory cell carcinoma of the bladder and basal cell carcinoma and adjuvant use with vaccines for HPV-associated cervical cancer. 55 More TLR4 agonists are currently in various stages of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Nontypeable Haemophilus influenzae (NTHi) is a risk factor for chronic obstructive pulmonary disease (COPD), which has been reported to promote lung cancer development in mice in a toll-like receptor (TLR)-dependent manner [ 88 , 89 ]. Further investigation revealed that NTHi promoted K-ras-driven lung cancer via COPD-like airway inflammation, which was mediated by the NF-κB-involved TLR2/4/9 pathway [ 89 ]. However, the correlation between NTHi and lung cancer in patients has not been fully elucidated [ 90 ], which, in turn, sheds light an opportunity for researchers to fill in this gap.…”
Section: Bacteria and Lung Cancermentioning
confidence: 99%